Analisis Kemampuan Manajemen Laba Memediasi Pengaruh Profitabilitas dan Leverage terhadap Nilai Perusahaan - Simorangkir, Melyanti; Suhartono, Sugi (Jurnal Akuntansi, 2025)
This research examines the impact of profitability and leverage on firm value, with earnings management serving as a mediating variable. Grounded in agency and signaling theories, the study employs secondary data from 44 non-cyclical consumer sector firms listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The findings reveal that both profitability and leverage exert a direct, positive, and significant influence on firm value. Furthermore, profitability is found to significantly affect earnings management. However, the results indicate that earnings management does not play a significant mediating role in the relationship between profitability or leverage and firm value.